2009
DOI: 10.1021/pr900103y
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae and Staphylococcus aureus Pneumonia Induce Distinct Metabolic Responses

Abstract: Pneumonia is an infection of the lower respiratory tract caused by microbial pathogens. Two such pathogens, Streptococcus pneumoniae and Staphylococcus aureus, are the most common causes of community-acquired and hospital-acquired pneumonia respectively. Each expresses strains highly resistant to penicillin and other antibiotics, and a significant number of people succumb to infection by these pathogens every year. Urinary metabolite changes in a C57Bl/6 mouse model with lung infection from either S. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 45 publications
2
77
0
Order By: Relevance
“…In particular, urine metabolomics is well suited for young children and in patients in whom venous access is problematic or for those who are averse to blood sampling. Notably, pathogen-specific changes in urine metabolites were detected in an experimental model of pneumonia (31). This was mimicked in the human situation, in which this approach successfully differentiated bacterial and viral pneumonias (32).…”
Section: Sample Handling and Preparationmentioning
confidence: 92%
“…In particular, urine metabolomics is well suited for young children and in patients in whom venous access is problematic or for those who are averse to blood sampling. Notably, pathogen-specific changes in urine metabolites were detected in an experimental model of pneumonia (31). This was mimicked in the human situation, in which this approach successfully differentiated bacterial and viral pneumonias (32).…”
Section: Sample Handling and Preparationmentioning
confidence: 92%
“…Additionally, metabolomics have been used to understand metabolic changes that occur during long-term bacterial infection 11 and even to improve diagnostic capabilities of community-acquired pneumonia. [12][13][14] There is a limited amount of data regarding metabolomic approaches in HIV-1-infected patients. Small studies have been done to characterize the profile of oral wash metabolites, 15 to identify differentially regulated metabolites in cerebrospinal fluid of SIV-infected monkeys 16 and humans 17 with central nervous system disease, and to investigate drug interactions and side effects.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that NMR spectroscopy coupled with targeted profiling techniques offers a powerful approach to generate high-density metabolic data on biofluids (3)(4)(5)(6)(7)(8). Multivariate statistical analysis, including principal component analysis (PCA), partial least-squares-discriminant analysis (PLS-DA), or orthogonal partial least-squares-discriminant analysis (OPLS-DA) can be applied to these data or complex spectral data to aid in the characterization of changes related to a biological perturbation or disease.…”
mentioning
confidence: 99%